Learning from fights: Males' social dominance status impact reproductive success in Drosophila melanogaster. - Antoine Prunier; Severine Trannoy (PLoS ONE, 2024)
In animals, the access to vital resources often relies on individuals' behavioural personality, strength, motivation, past experiences and dominance status. Dominant individuals would be more territorial, providing them with a better access to food resources and mate. The so-called winner and loser effects induce individuals' behavioural changes after experiencing a victory or a defeat, and lead to an individual persistent state influencing the outcome of subsequent fights. However, whether and how development of winner and loser effects affect individuals' fitness is controversial. The aim of this study is to evaluate how individuals' fitness can be influenced by previous fighting experience in Drosophila melanogaster. In this study, we assess various behavioural performances as indicators for dominant and subordinate fitness. Our results show that subordinates are less territorial than dominants although their locomotor abilities are not affected. We also demonstrate that in a non-competitive context, experiencing a defeat reduces males' motivation to court females but not the reproductive success while in a competitive context, it negatively affects males' reproductive success. However, we found no impact upon either males' ability to distinguish potential mates nor on females' choice of a specific mating partner. Overall, these results indicate that previous defeats reduce reproductive success, a commonly used estimate of individual fitness.